Marketing Global: Studi Kasus Coca-Cola Company - Diky Erdia Wahendra; Christian Stevan Klose Situmorang; Muhammad Fadil Fadhlullah; Ahmad Vajri Rahman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to examine the global marketing strategies implemented by The Coca-Cola Company in maintaining its competitive position in international markets. The advancement of globalization requires multinational corporations to design marketing strategies that are not only globally standardized but also adaptable to local market characteristics and consumer needs. This research employs a descriptive qualitative method with a case study approach, conducted through the review of relevant literature, corporate reports, and academic journals. The findings indicate that Coca-Cola’s success in global marketing is supported by strong brand differentiation, an extensive global distribution network through partnerships with bottlers, and the application of the glocalization concept, which balances standardization and adaptation within the marketing mix. Furthermore, market expansion strategies are implemented systematically through the selection of target markets based on growth potential, accessibility, and competitive intensity. The study also reveals that the country of origin image of the United States serves as a positive brand asset by creating aspirational value and quality perceptions across various markets, although in certain contexts it also presents challenges that require strategic management. Overall, this study confirms that Coca-Cola’s global marketing strategy is capable of achieving sustainable competitive advantage through the integration of strong global branding, product innovation, and responsiveness to local market dynamics.